Research traditions of innovation: Goods-dominant logic, the resource-based approach, and service-dominant logic. Issue 6 (4th November 2014) - Mele, Cristina; Colurcio, Maria; Russo-Spena, Tiziana
Abstract : Purpose: – The purpose of this paper is to offer a fresh framing of innovation, as service innovation/value innovation. Design/methodology/approach: – By examining the visions, patterns and outcomes of three different research approaches to understanding innovation – goods-dominant (G-D) logic, the resource-based approach and service-dominant (S-D) logic – the authors strive to outline the contribution of each to the debate on innovation. This investigation involves a comprehensive literature review. Scrutiny of a case company provides a means of identifying and illustrating how these approaches play out in a real business context. Findings: – A framework for innovation builds on the comparison of the three research approaches. G-D logic, when analysed in terms of new product development and new service development, positions innovation as an output (a new good or service) of a business's internal processes, with the firm as the main actor. The resource-based approach establishes the drivers of innovation as knowledge, capabilities and relationships, but the firm is still the main innovator. S-D logic addresses "open" innovation processes in which all actors in the network can mobilize and integrate their resources to become value co-innovators. Research limitations/implications: – This study builds on the literature review by offering a more systematic way of dealing with the different research traditions in innovation debate. Practical implications: – This study spurs managers to question the validity of dominant logic and how it affects the decision-making process. The conceptualization of innovation within S-D logic provides new avenues for decision makers and practitioners to tackle topical challenges of global competition. Originality/value: – The value of this paper lies in defending the premise that S-D logic is better suited than the other two research traditions to frame current innovation within the context of global competition because it moves innovation beyond mainstream conceptualization: from "products and services" to "service and value", from "buyer-seller dyads" to "ecosystem relationships", and from "closed/linear process" to "open/co-created process".